Community-Based Entrepreneurship Learning through Pyrography Training for Forest Product Technology Students - Ainun Zalsabila; Erwin; Alfia Dewi Fadwati (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
Students in the Forest Product Technology programme often possess theoretical knowledge of wood but lack practical competencies in creative product development and forest-based enterprise management. This community engagement initiative addressed that gap through a structured pyrography training programme conducted in partnership with WoodCraft SMEs in Loa Janan, Samarinda, whilst simultaneously strengthening the capacity of partner SMEs through product innovation and the expansion of academic networks. Using a Community-Based Learning (CBL) approach grounded in Knowledge-Based Community Development, the programme positioned students as agents of innovation, academics as facilitators, and the SME as a practical mentor. A total of 25 students from the 2021–2023 cohorts participated in practitioner presentations, production process observations, and hands-on pyrography practice. Outcomes demonstrated measurable improvements in students' understanding of pyrography techniques, local timber characteristics, and basic business management. Active participation throughout the sessions indicated a substantial strengthening of entrepreneurial competencies. For WoodCraft Samarinda, the programme generated increased business exposure and expanded academic networks. This initiative represents a replicable model of university–SME collaboration for building a sustainable, local-resource-based entrepreneurial ecosystem in the context of forestry higher education.